2020
DOI: 10.1186/s41065-020-00143-z
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral and segmental distribution of facial erythema: is it a real port-wine stain?

Abstract: Capillary malformation-arteriovenous malformations (CM-AVMs) caused by a RASA-1 or EPHB4 mutation are characterized as hereditary sporadic or multifocal capillary malformations (CMs), associated with potential fast-flow vascular anomalies underlying erythema lesions. Because of the similar phenotype, CM-AVMs should be considered in the differential diagnosis of isolated CMs as well as other disorders with an erythema phenotype, such as hereditary hemorrhagic telangiectasia (HHT). Herein, we report a male patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Cutaneous redness or erythema can be seen in many vascular anomalies, such as port-wine stains, hereditary hemorrhagic telangiectasia, and arteriovenous malformations. 23 It is also one of the most common clinical symptoms among AVMs patients. 1 In previous studies, 83% to 100% of the patients have been reported with skin redness.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous redness or erythema can be seen in many vascular anomalies, such as port-wine stains, hereditary hemorrhagic telangiectasia, and arteriovenous malformations. 23 It is also one of the most common clinical symptoms among AVMs patients. 1 In previous studies, 83% to 100% of the patients have been reported with skin redness.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although they are most often distributed randomly across the body, occasionally, these malformations can be limited to specific areas such as the face. 3 CM-AVM type 2 can also be associated with AVM or fistulas (seen in 18% of patients), typically in the skin, muscle, bone, brain, or spinal cord. Sometimes, the Parkes-Weber syndrome phenotype is seen, with multiple arteriovenous fistulas leading to soft-tissue and skeletal hypertrophy of the affected limb.…”
Section: Capillary Malformation-arteriovenous Malformation Capillary ...mentioning
confidence: 99%
“…Doppler pulsation can be found even in minor CMs and is explained by an arterial component in the CMs ( 14 , 15 ). As a consequence a higher skin temperature or thrill in the affected area can be observed ( 10 ). Fast-flow malformations, such as AVMs/ AVFs, can be present in different sizes and locations.…”
Section: Capillary Malformation-arteriovenous Malformation Syndrome-1...mentioning
confidence: 99%
“…The most relevant differential diagnoses to CM-AVM2 are CM-AVM1, HHT, Sturge-Weber syndrome (SWS) and Klippel-Trenaunay syndrome (KTS) ( 10 , 11 , 17 , 18 ).…”
Section: Capillary Malformation-arteriovenous Malformation Syndrome-1...mentioning
confidence: 99%
See 1 more Smart Citation